Social and Personal Issues in Noli Me Tangere: A Contemporary Analysis - Largo, Rowena C; Largo, Rowena (Eximia, 2025)
The novel Noli Me Tangere is a literary work that shaped and awakened Filipino consciousness and the history of the Philippines. Rizal was inspired to write Noli Me Tangere after reading Uncle Tom’s Cabin by Harriet Beecher Stowe, which depicted the suffering of Black slaves under white American masters and their cruelty and abuse. He compared this to the plight of Filipinos under Spanish rule. A deeper analysis of Noli Me Tangere can be used in teaching Filipino literature in schools, emphasizing how literature serves as a powerful tool in exposing social issues that remain relevant today. It highlights the role of literature in shaping national identity and unity among Filipinos. Almario (2011) noted that the novel’s main characters were not only created for dramatic storytelling but also to represent the thoughts and behaviors of different Filipinos during that time. This proves that the characters play a crucial role in connecting the past to the present. The Qualitative Research Method was used in the form of Content Analysis to examine selected characters from Noli Me Tangere, focusing on character portrayal, ideas, social issues, and their relevance to contemporary society. Dr. Jose Rizal’s Noli Me Tangere reflects the true state of Philippine society during the Spanish colonial era. It reveals the impact of colonialism, corruption, and the abuses of the church and government on ordinary citizens. Its characters represent different sectors of society and illustrate social problems that persist to this day. The lessons and awareness from the novel continue to inspire Filipinos to fight for their rights and freedom.